Lithium adsorbent, preparation method thereof and method for extracting lithium from lithium-containing waste
By using a complex of a metal organic frame and persulfate as a lithium adsorbent, lithium elements are efficiently extracted from lithium iron phosphate, and the problem of high energy consumption and cost in the existing technology is solved, and the green and economical lithium recycling effect is achieved.
Patent Information
- Application Number
- CN202411277020.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-11
- Publication Date
- 2025-04-11
AI Technical Summary
The prior art methods for extracting lithium elements from lithium iron phosphate have problems such as high energy consumption, no advantage in cost and low economic benefits.
A lithium adsorbent is used, which consists of a metal organic frame and a persulfate complexed on the metal organic frame. This material forms a complex by combining persulfate with transition metal ions and organic molecular ligands, increasing the contact area between persulfate and lithium-containing raw materials, improving the reaction efficiency and lithium recovery rate.
It realizes efficient, green and economical lithium element extraction, improves lithium recovery and selectivity, and reduces energy consumption and production costs.
Smart Images

Figure CN119793417A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of lithium recovery, and in particular to a lithium adsorbent and a preparation method thereof, and a method for extracting lithium from lithium-containing waste materials. Background Art
[0002] In recent years, with the advancement of science and technology, the lithium-ion battery industry has developed rapidly, and the battery industry has become the largest consumer of lithium. Due to the excellent electrochemical properties and high safety of lithium iron phosphate, lithium iron phosphate batteries have attracted much attention. Generally speaking, the retirement cycle of lithium-ion batteries is about 3 years. At present, a large number of lithium iron phosphate batteries have begun to be retired. From the perspective of environmental protection and resource recycling, it is necessary to recover lithium from waste lithium iron phosphate.
[0003] At present, the relevant technology recovers lithium from lithium iron phosphate by adding oxidants. This method requires high energy consumption, does not have cost advantages, has average competitiveness, and is not suitable for industrial production. Therefore, it is urgent to develop a green, economical and efficient lithium extraction technology. Summary of the invention
[0004] This application is based on the inventor's discovery and understanding of the following facts and problems:
[0005] At present, the oxidants for extracting lithium from lithium iron phosphate include one or a mixture of persulfate, ozone, oxygen, hypochlorite, and hydrogen peroxide, but there are still the following shortcomings:
[0006] (1) Sodium persulfate is used as an oxidant, but the amount of sodium persulfate used is relatively high, and the price of sodium sulfate is relatively expensive, so its excessive amount makes this method not cost-effective;
[0007] (2) At present, the reaction of extracting lithium from lithium iron phosphate generally requires heating and a long reaction time. The higher the reaction temperature, the longer the reaction time, which means higher energy consumption, making the cost more disadvantageous;
[0008] (3) The leaching rate of lithium elements in lithium iron phosphate is average and the economic benefits are not high.
[0009] The present application aims to solve at least one of the technical problems in the related art to a certain extent. To this end, the present application proposes an efficient, green and economical lithium adsorbent and a preparation method thereof, as well as a method for extracting lithium from lithium-containing waste.
[0010] In the first aspect of the present application, a lithium adsorbent is proposed, comprising a metal organic framework and a persulfate complexed on the metal organic framework; wherein the metal organic framework comprises a complex of transition metal ions and organic molecular ligands. In the lithium adsorbent, the metal organic framework material can provide sufficient complexing sites, so that the persulfate can be effectively complexed on the metal organic framework material. In the process of recovering lithium using the lithium adsorbent, the contact area between the persulfate and the lithium-containing raw material can be effectively increased, the reaction efficiency is greatly improved, and the selectivity of recovering lithium is improved. At the same time, the metal organic framework can provide sufficient adsorption sites to adsorb lithium released from the lithium-containing raw material, which can further improve the recovery rate and selectivity of lithium.
[0011] In some embodiments, the persulfate includes at least one of ammonium persulfate, sodium persulfate, and potassium persulfate. Thus, the material has a wide source and can effectively react with lithium-containing waste to release lithium, thereby achieving the purpose of recovering lithium.
[0012] In some embodiments, the transition metal ion includes at least one of Co, Fe, Zn, Mn, Cu, and Cr; in other embodiments, the transition metal ion is at least one of Co, Zn, and Fe. Thus, it can coordinate with organic molecules to form a metal organic framework structure, which can provide S2O8 2- The adsorption sites can also provide space for the subsequent lithium adsorption.
[0013] In some embodiments, the organic molecular ligand includes a 2-methylimidazole ligand, which is beneficial for constructing a metal organic framework, thereby providing sufficient complexing sites and adsorption sites, and achieving efficient and highly selective recovery of lithium.
[0014] In some embodiments, the complex has the following chemical formula:
[0015] M1 a M2 b S2O8 / MI
[0016] Among them, 1≥a≥0, 1≥b≥0, and a and b meet the requirements of chemical formula balancing;
[0017] M1 includes at least one of NH4, Na, and K,
[0018] M2 includes at least one of Co, Fe, Zn, Mn, Cu, and Cr; in some other embodiments, M2 is at least one of Co, Zn, and Fe;
[0019] MI includes 2-methylimidazole ligands. Thus, different metal ion radii can be used to form metal organic framework structures with different pore sizes and different adsorption capacities for persulfate, thereby improving the recovery rate of lithium.
[0020] In some embodiments, the molar ratio of the persulfate in the persulfate to the transition metal ion is 4:1 to 1:4; in other embodiments, the molar ratio of the persulfate in the persulfate to the transition metal ion is 2:3 to 1:4.
[0021] In some embodiments, the molar ratio of the persulfate ion to the organic molecule ligand is 1:10 to 1:1; in other embodiments, the molar ratio of the persulfate ion to the organic molecule ligand is 1:4 to 1:1.
[0022] Within the above-mentioned ratio range, the metal organic framework has good adsorption capacity, which is beneficial to increase the contact area between the persulfate ion and the lithium-containing raw material during the reaction process, can effectively improve the reaction efficiency, and promote the improvement of the lithium recovery rate and the purity of the obtained lithium.
[0023] In some embodiments, the specific surface area of the lithium adsorbent is 12 m 2 / g~18m 2 / g(such as 12m 2 / g, 13m 2 / g, 14m 2 / g, 15m 2 / g, 16m 2 / g, 17m 2 / g or 18m 2 In some embodiments, the porosity of the lithium adsorbent is 8% to 30% (such as 8%, 12%, 16%, 20%, 24% or 30%), which is beneficial to increase the adsorption sites of the lithium adsorbent, thereby achieving efficient recovery of lithium.
[0024] In some embodiments, the lithium adsorbent includes secondary particles formed by agglomeration of primary particles, wherein:
[0025] The D of the primary particles 50 The particle size is 0.8 microns to 1.5 microns; in other embodiments, the primary particle D 50 The particle size is 1.0 micron to 1.2 micron. In some embodiments, the secondary particles have a D 50 The particle size is 5 microns to 15 microns; in some other embodiments, the secondary particles have a D 50 The particle size is preferably 5 microns to 8 microns. Within the above particle size range, the lithium adsorbent has a better adsorption effect on lithium.
[0026] The second aspect of the present application provides a method for preparing a lithium adsorbent, comprising: mixing a persulfate, a transition metal salt and a solvent to obtain a mixed salt solution; mixing an organic molecular ligand with the solvent to obtain an organic solution; mixing the mixed salt solution and the organic solution and performing a first stirring, and sequentially concentrating and filtering the obtained mixture to obtain the lithium adsorbent.
[0027] The preparation method is simple to operate, economical and environmentally friendly, and can be easily industrialized for production. The prepared lithium adsorbent has a high adsorption capacity for lithium.
[0028] In some embodiments, mixing the mixed salt solution and the organic solution comprises: adding the mixed salt solution dropwise to the organic solution under heating and the first stirring condition, thereby facilitating the formation of a metal organic framework, thereby realizing the recovery of lithium.
[0029] In some embodiments, the heating temperature is 90°C to 105°C; and / or the first stirring speed is 200rpm to 600rpm; and / or after the mixed salt solution is added, the first stirring is continued for 30min to 60min. This allows the reaction to proceed smoothly, thereby forming a metal organic framework and achieving the purpose of efficient lithium adsorption and recovery.
[0030] In some embodiments, the total concentration of salt in the mixed salt solution is 0.5 mol / L to 1 mol / L; and / or the transition metal salt includes at least one of nitrate, oxalate, and sulfate, specifically nitrate; and / or the concentration of the organic solution is 1 mol / L to 5 mol / L; and / or the solvent includes at least one of alcohol and water, specifically water. This is conducive to forming a metal organic framework, thereby achieving efficient recovery of lithium.
[0031] The third aspect of the present application proposes a method for extracting lithium from lithium-containing waste, comprising: preheating a solution containing a lithium adsorbent and a solution containing lithium-containing waste respectively to obtain a preheated lithium adsorbent solution and a preheated lithium-containing solution; mixing the preheated lithium adsorbent solution and the lithium-containing solution, and stirring the obtained mixed solution for a second time while maintaining the preheating temperature, and separating the solid and liquid to obtain a solid material and a lithium-rich mother liquor; concentrating and precipitating lithium in the lithium-rich mother liquor in turn to obtain a lithium-containing product. The method is simple to operate, can efficiently extract lithium from lithium-containing waste, has a high lithium recovery rate, and the recovered lithium has a high purity.
[0032] In some embodiments, the preheating temperature is 40°C to 90°C; in other embodiments, the preheating temperature is 40°C to 65°C; in some specific examples, the preheating temperature is 60°C to 65°C; and / or the preheating time is 5min to 10min. This can provide the energy required for the cleavage of the oxygen-oxygen bond in the persulfate, generate sulfate radicals with stronger oxidizing properties, and facilitate the subsequent extraction of lithium.
[0033] In some embodiments, the preheated lithium adsorbent solution and the lithium-containing solution are mixed in a ratio of 1:0.55 to 1 in molar ratio of lithium element in the lithium-containing solution to persulfate in the lithium adsorbent solution. Within the above ratio range, the lithium adsorbent has a better adsorption effect on lithium.
[0034] In some embodiments, the pH value of the mixed solution is 1-14; in other embodiments, the pH value of the mixed solution is 1-7; in some specific examples, the pH value of the mixed solution is 3-5.
[0035] In some embodiments, the solid-liquid ratio of the mixed solution is 100 g / L to 300 g / L; in other embodiments, the solid-liquid ratio is 250 g / L to 300 g / L.
[0036] In some embodiments, the second stirring speed is 400 rpm to 1000 rpm. In some embodiments, the second stirring time is 10 min to 10 h; in other embodiments, the second stirring time is 10 min to 30 min. Within the above parameter range, the reaction is more fully carried out and the recovery rate of lithium is higher.
[0037] In some embodiments, the concentration and lithium precipitation include: continuously evaporating the lithium-rich mother liquor until turbidity occurs to obtain a concentrated solution; mixing the concentrated solution with a lithium precipitation promoter and performing a third stirring to obtain the lithium-containing product. This can promote precipitation, thereby obtaining a lithium-containing product.
[0038] In some embodiments, the lithium precipitation comprises: mixing the concentrated solution and a lithium precipitation accelerator, adjusting the pH of the obtained mixture to 8-10, and performing the third stirring to obtain the lithium-containing product. This is conducive to precipitation, thereby obtaining a lithium-containing product.
[0039] In some embodiments, the temperature of the continuous evaporation is 90° C. to 105° C. This is beneficial for concentrating the lithium-rich mother liquor and then performing subsequent reactions.
[0040] In some embodiments, the lithium precipitation promoter includes at least one of sodium carbonate, ammonium carbonate, potassium carbonate, and carbon dioxide.
[0041] In some embodiments, the molar ratio of the lithium precipitation promoter to the lithium element in the lithium-containing waste is 0.55-0.6:1.
[0042] In some embodiments, the third stirring speed is 400 rpm to 1000 rpm.
[0043] In some embodiments, the third stirring time is 30 min to 1 h.
[0044] Therefore, the above reaction conditions are conducive to the smooth progress of the reaction and obtaining a lithium-containing product.
[0045] In some embodiments, after the lithium precipitation step, the process further comprises: dispersing the product of the lithium precipitation step with hot water at 50°C to 90°C, filtering and drying in sequence to obtain the lithium-containing product. Thus, a high-purity lithium-containing product can be obtained.
[0046] In some embodiments, the lithium-containing waste material includes at least one of lithium iron phosphate battery positive electrode black powder and lithium iron phosphate battery positive and negative electrode waste powder. Therefore, the lithium-containing waste material has a wide range of sources, and the lithium adsorbent of the present application has a wide range of applications. BRIEF DESCRIPTION OF THE DRAWINGS
[0047] Figure 1 It is a hydrogen peroxide molecule, S2O8 2- Schematic diagram of the molecular structure.
[0048] Figure 2 This is a scanning electron microscope image of the lithium adsorbent of Example 3 of the present application.
[0049] Figure 3 This is a scanning electron microscope image of the lithium adsorbent of Example 6 of the present application.
[0050] Figure 4 This is a scanning electron microscope image of the lithium adsorbent of Example 7 of the present application. DETAILED DESCRIPTION
[0051] The embodiments of the present application are described in detail below, and examples of the embodiments are shown in the accompanying drawings. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present application, but cannot be understood as limiting the present application.
[0052] In a first aspect of the present application, a lithium adsorbent is provided, comprising a metal organic framework and a persulfate complexed on the metal organic framework; wherein the metal organic framework comprises a complex of a transition metal ion and an organic molecular ligand.
[0053] It can be understood that the lithium adsorbent of the present application is a complex of a metal organic framework and persulfate. The metal organic framework material can provide sufficient complexation sites for persulfate. In the process of recovering lithium using the lithium adsorbent, the contact area between the persulfate and the lithium-containing raw material can be effectively increased, the reaction efficiency can be greatly improved, and the selectivity of lithium recovery can be improved. The strong oxidizing property of persulfate can promote the release of lithium from lithium-containing waste. At the same time, the metal organic framework can provide sufficient adsorption sites for the released lithium, thereby realizing efficient adsorption and recovery of lithium.
[0054] In some embodiments, the persulfate includes at least one of ammonium persulfate, sodium persulfate, and potassium persulfate. Thus, the persulfate can effectively react with the lithium-containing material to efficiently recover lithium.
[0055] In some embodiments, the transition metal ion includes at least one of Co, Fe, Zn, Mn, Cu, and Cr; in other embodiments, the transition metal ion is at least one of Co, Zn, and Fe. Thus, it can effectively coordinate with the organic molecular ligand to form a metal organic framework structure with abundant pores and complexing sites to adsorb persulfate, and also provide space for the subsequent adsorption of lithium. Furthermore, different transition metal ions have different radii, and can form metal organic framework structures with different pore sizes and different adsorption capacities for persulfate, so that the metal organic framework structure can be appropriately regulated by the selection of transition metals.
[0056] In some embodiments, the organic molecular ligand includes 2-methylimidazole, thereby being more conducive to forming a metal organic framework structure with abundant pores and complexing sites.
[0057] In some embodiments, the complex has the following formula:
[0058] M1 a M2 b S2O8 / MI
[0059] Among them, 1≥a≥0, 1≥b≥0, and a and b meet the requirements of chemical formula balancing;
[0060] M1 includes at least one of NH4, Na, and K,
[0061] M2 includes at least one of Co, Fe, Zn, Mn, Cu, and Cr; in some other embodiments, M2 is at least one of Co, Zn, and Fe;
[0062] MI includes 2-methylimidazole.
[0063] With the above chemical formula, the metal organic framework has abundant pores and complexing sites, which can effectively complex persulfate, and thus can greatly increase the contact area between the lithium adsorbent and the lithium-containing material when recovering lithium, greatly improving the reaction efficiency.
[0064] It should be noted that, in order to simplify the expression, the different ratios of persulfate and organic molecular ligands to transition metal ions are not reflected in the chemical formula. That is to say, the persulfate and organic molecular ligands in the chemical formula are not shown with specific subscripts, and their specific ratios are not limited, which can be the ratio range of conventional coordination compounds.
[0065] In some embodiments, the molar ratio of persulfate to transition metal ion in persulfate is 4:1 to 1:4; in other embodiments, the molar ratio of persulfate to transition metal ion in persulfate is 2:3 to 1:4. Within this ratio range, the lithium adsorbent has a better effect of recovering lithium.
[0066] In some embodiments, the molar ratio of persulfate to organic molecule ligand is 1:10 to 1:1; in other embodiments, the molar ratio of persulfate to organic molecule ligand is 1:4 to 1:1; specifically, 1:10, 1:9, 1:8, 1:7, 1:6, 1:5, 1:4, 1:31:2, 1:1, etc. Within the above ratio range, the metal organic framework has abundant pores and adsorption sites, has good adsorption capacity, and the lithium adsorbent has a better effect of recovering lithium.
[0067] In some embodiments, the specific surface area of the lithium adsorbent is 12 m 2 / g~18m 2 / g(such as 12m 2 / g, 13m 2 / g, 14m 2 / g, 15m 2 / g, 16m 2 / g, 17m 2 / g or 18m 2 / g, etc.). In some embodiments, the porosity of the lithium adsorbent is 8% to 30% (such as 8%, 12%, 16%, 20%, 24% or 30%, etc.). The specific surface area and porosity of the lithium adsorbent are within the above ranges, which is beneficial to increase the adsorption sites of the lithium adsorbent, thereby improving the recovery rate of lithium.
[0068] In some embodiments, the lithium adsorbent includes secondary particles formed by agglomeration of primary particles, wherein: 50 The particle size may be 0.8 μm to 1.5 μm (specifically 0.8 μm, 0.9 μm, 1 μm, 1.1 μm, 1.2 μm, 1.3 μm, 1.4 μm, 1.5 μm, etc.); in other embodiments, the D 50The particle size may be 1.0 μm to 1.2 μm. In some embodiments, the secondary particles have a D 50 The particle size is 5 μm to 15 μm (specifically 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, etc.); in other embodiments, the secondary particles have a D 50 The particle size is 5 microns to 8 microns. Within the above particle size range, the lithium adsorbent has a better adsorption effect on lithium.
[0069] In a second aspect of the present application, a method for preparing a lithium adsorbent is proposed, comprising:
[0070] S10: mixing persulfate, transition metal salt and solvent to obtain a mixed salt solution.
[0071] In this step, there is no particular restriction on the specific manner of mixing the persulfate, transition metal salt and solvent, and there is no particular restriction on the mixing order. For example, the persulfate and transition metal salt can be added to the solvent separately or simultaneously, the persulfate and transition metal salt can be mixed first, and then the obtained mixed salt can be added to the solvent, etc., and the present application has no particular restriction.
[0072] In some embodiments, the transition metal salt may include at least one of nitrate, oxalate, and sulfate; in other embodiments, the transition metal salt is nitrate. In some embodiments, the transition metal in the transition metal salt may include at least one of Co, Fe, Zn, Mn, Cu, and Cr; in other embodiments, the transition metal ion is at least one of Co, Zn, and Fe. Thus, it has better complexing ability and can effectively complex with organic molecules and persulfate.
[0073] In some embodiments, the persulfate may include at least one of ammonium persulfate, sodium persulfate, and potassium persulfate. Thus, the material has a wide source and can effectively react with lithium-containing waste to release lithium, thereby achieving the purpose of recovering lithium.
[0074] In some embodiments, the total concentration of salt in the mixed salt solution (i.e., the sum of the concentrations of persulfate and transition metal salt) is 0.5 mol / L to 1 mol / L, such as 0.5 mol / L, 0.6 mol / L, 0.7 mol / L, 0.8 mol / L, 0.9 mol / L, 1 mol / L, etc. The molar ratio of persulfate ion in the persulfate to the transition metal ion is 4:1 to 1:4, such as 2:3 to 1:4, etc.
[0075] In some embodiments, the concentration of the organic solution is 1 mol / L to 5 mol / L (eg, 1 mol / L, 2 mol / L, 3 mol / L, 4 mol / L, or 5 mol / L, etc.).
[0076] In some embodiments, the solvent may include at least one of alcohol and water; in some specific examples, the solvent is water.
[0077] S20: mixing the organic molecular ligand with the solvent to obtain an organic solution.
[0078] In this step, the specific method of mixing the organic molecules and the solvent is not particularly limited and can be flexibly selected according to actual needs. For example, the organic molecules can be added to the solvent and mixed evenly.
[0079] In some embodiments, the organic molecule includes 2-methylimidazole, which is beneficial for constructing a metal organic framework, thereby providing sufficient complexation sites and adsorption sites to achieve efficient and highly selective recovery of lithium.
[0080] In some embodiments, the solvent used in this step is the same as the solvent used in the mixed salt solution. In this way, the consistency of the reaction system can be maintained, which is conducive to the smooth progress of the reaction.
[0081] In some embodiments, the concentration of the organic solution may be 1 mol / L to 5 mol / L, such as 1 mol / L, 2 mol / L, 3 mol / L, 4 mol / L, 5 mol / L, etc. This concentration range can take into account both the reaction speed and the reaction efficiency, and is conducive to the efficient preparation of a lithium adsorbent with better performance.
[0082] S30: mixing the mixed salt solution and the organic solution and performing a first stirring, and sequentially concentrating and filtering the obtained mixture to obtain the lithium adsorbent.
[0083] In some embodiments, the mixed salt solution and the organic solution are mixed at a ratio of 1:10 to 1:1 (specifically 1:10, 1:9, 1:8, 1:7, 1:6, 1:5, 1:4, 1:3, 1:2, 1:1, etc.) of the molar ratio of persulfate to organic molecular ligand; in other embodiments, the mixed salt solution and the organic solution are mixed at a ratio of 1:4 to 1:1 of the molar ratio of persulfate to organic molecular ligand. Thus, a lithium adsorbent with better performance is obtained.
[0084] In some embodiments, mixing the mixed salt solution and the organic solution comprises: adding the mixed salt solution dropwise to the organic solution under heating and first stirring conditions, thereby facilitating the full formation of the metal organic ligand precursor.
[0085] In some embodiments, the heating temperature may be 90°C to 105°C (specifically 90°C, 91°C, 92°C, 93°C, 94°C, 95°C, 96°C, 97°C, 98°C, 99°C, 100°C, 101°C, 102°C, 103°C, 104°C, 105°C, etc.). Within this temperature range, organic molecular ligands, persulfate and transition metal complexation are facilitated to form a lithium adsorbent with better performance.
[0086] In some embodiments, the first stirring speed is 200 rpm to 600 rpm (eg, 200 rpm, 300 rpm, 400 rpm, 500 rpm or 600 rpm, etc.), thereby facilitating the reactants to fully contact and achieving higher reaction efficiency.
[0087] In some embodiments, after the mixed salt solution is added dropwise, the first stirring is continued for 30 to 60 minutes, thereby facilitating the full complexation reaction of the organic molecular ligand, the persulfate and the transition metal to obtain a lithium adsorbent with better performance.
[0088] In some embodiments, the mixture obtained after the first stirring is concentrated by evaporation to increase the product concentration.
[0089] In some embodiments, filtering the concentrated product can further purify the lithium product.
[0090] In some specific embodiments of the present application, the method for preparing a lithium adsorbent may include:
[0091] S1. A persulfate (at least one of ammonium persulfate, potassium persulfate, and sodium persulfate) and a transition metal salt (one of transition metal salts such as Co, Fe, Zn, Mn, Cu, Cr (including but not limited to nitrate, oxalate, sulfate, etc.)) are added at a molar ratio of 4:1 to 1:4 to prepare a solution A with a total concentration of 0.5 mol / L to 1 mol / L. The solvent may be alcohol or water.
[0092] S2, prepare a 1 mol / L to 5 mol / L organic solution (solution B) at room temperature, keeping the solvent the same as S1;
[0093] S3, under stirring at 200 rpm-600 rpm and 90 degrees Celsius-105 degrees Celsius, gradually add solution B to the stirring solution A, and the ratio of the two is designed according to the chemical formula, wherein the molar number of persulfate in solution A: the molar number of organic molecules in solution B is 1:10-1:1;
[0094] S4, after stirring for 30 minutes, the obtained mixed solution C was concentrated and filtered to finally obtain the target product: M1 a M2 b S2O8 / MI.
[0095] In a third aspect of the present application, a method for extracting lithium from lithium-containing waste is proposed, comprising:
[0096] S100: preheating the solution containing the lithium adsorbent and the solution containing the lithium-containing waste respectively to obtain a preheated lithium adsorbent solution and a preheated lithium-containing solution.
[0097] The lithium adsorbent of the present application performs well in a wide pH range, so the present application has no particular restrictions on the source and specific type of lithium-containing waste. In some embodiments, the lithium-containing waste may include at least one of lithium iron phosphate battery positive electrode black powder and lithium iron phosphate battery positive and negative electrode waste powder. The following description is based on lithium iron phosphate waste as an example.
[0098] It can be understood that lithium-containing waste can be obtained by disassembling waste lithium iron phosphate batteries. As an example, waste lithium iron phosphate batteries can be discharged, coarsely crushed, pyrolyzed, finely crushed, and sorted in sequence to obtain electrode positive and negative waste powders, copper powder, aluminum powder, and iron powder. In addition, positive electrode sheet powder can also be obtained by discharging, disassembling, and pyrolysis. Among them, the pyrolysis temperature can be 450℃~600℃; in other embodiments, the pyrolysis temperature is 450℃~550℃; in some specific examples, the pyrolysis temperature is 450℃, which can make the separation rate of aluminum foil and positive lithium iron phosphate powder reach 99.99%; and the pyrolysis atmosphere can be nitrogen or argon, and the insulation time can be 2 hours to 8 hours.
[0099] In some embodiments, the preheating temperature is 40°C to 90°C; in other embodiments, the preheating temperature is 40°C to 65°C; in some specific examples, the preheating temperature is 60°C to 65°C; specifically, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, etc. In some embodiments, the preheating time is 5 min to 10 min (such as 5 min, 6 min, 7 min, 8 min, 9 min or 10 min, etc.).
[0100] In the preheating step, the persulfate in the lithium adsorbent can generate a certain concentration of sulfate radicals and / or hydroxyl radicals under the action of thermal energy, so that the sulfate radicals and / or hydroxyl radicals with stronger oxidizing properties and selectivity can react with the lithium-containing waste material first, and in the subsequent reaction process, the reaction of sulfate radicals and / or hydroxyl radicals with the lithium-containing waste material is mainly based, thereby effectively improving the recovery rate and selectivity of lithium.
[0101] It is understandable that Figure 1 As shown in the figure, similar to the structure of hydrogen peroxide, persulfate (PMS) is formed by the two H atoms in H2O2 being replaced by HSO3- The symmetrical peroxide obtained by substitution. After the H atom in H2O2 is replaced, the bond length of the OO bond increases and the bond energy decreases. The OO bond length of PMS is 1.460nm. Its bond energy is generally 140kJ·mol -1 ~213.3 kJ·mol -1 within the range.
[0102] Therefore, theoretically, persulfate can -1 ~213.3 kJ·mol -1 ) under the action of , the OO bond can be broken. The reaction equation is as follows:
[0103] SO4 2- + heat energy = 2SO4 -
[0104] Therefore, as long as the heat energy exceeding the breaking of the OO bond in the sulfate group is applied, sulfate radicals (SO4· - ), and compared with persulfate, sulfate radicals and hydroxyl radicals have stronger oxidizing properties and selectivity. In the lithium recovery process, lithium can be leached more quickly and efficiently, and a higher lithium leaching rate and recovery rate can be achieved in a shorter time. The recovered lithium has a higher purity, which can greatly improve production efficiency and competitiveness.
[0105] S200: mixing the preheated lithium adsorbent solution and the lithium-containing solution, and performing a second stirring on the obtained mixed solution while maintaining the preheating temperature, and performing solid-liquid separation to obtain a solid material and a lithium-rich mother solution.
[0106] In this step, the lithium adsorbent can react with the lithium-containing waste to release the lithium element in the lithium-containing waste. The lithium element enters the solution, while other elements enter the solid phase, thereby achieving the separation and recovery of the lithium element. Taking lithium iron phosphate as an example, the specific reaction process is as follows:
[0107] Fe 2+ +SO4 - =Fe 3+ +SO4 2-
[0108] That is, sulfate free radicals oxidize the divalent iron in the lithium iron phosphate into trivalent iron, the lithium iron phosphate dissolves, and the lithium element enters the solution.
[0109] In some embodiments, the preheated solution containing the lithium adsorbent and the lithium-containing solution are mixed in a ratio such that the molar ratio of lithium in the lithium-containing solution to persulfate in the lithium adsorbent solution is 1:0.55 to 1 (specifically, 1:1, 0.9:1, 0.8:1, 0.7:1, 0.6:1, 0.5:1, 0.55:1, etc.). Thus, the effect of lithium recovery is better, and there is no waste of raw materials.
[0110] The lithium adsorbent of the present application has a good effect of recovering lithium in a relatively wide pH value range and can function well under acidic and alkaline conditions. Therefore, the present application has no special limitation on the pH value of the mixed solution. In some embodiments, the pH value of the mixed solution can be 1 to 14 (such as 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, etc.).
[0111] In some embodiments, under alkaline conditions, sulfate radicals can be converted into hydroxyl radicals during heating, and the reaction process is as follows:
[0112] SO4· - +H2O=SO4 2- +·OH+H +
[0113] SO4· - +OH - =SO4 2- +·OH
[0114] Based on the above principle, it can be known that in the present application, under acidic conditions, the main radical in the reaction system is the sulfate radical. When 7 < pH < 9, both the sulfate radical and the hydroxyl radical coexist. When pH > 9, the hydroxyl radical is the main one. Both the sulfate radical and the hydroxyl radical have strong oxidizing properties and can efficiently recover lithium. Relatively speaking, the effect of the sulfate radical in recovering lithium is better. Therefore, in some other embodiments, the pH value of the mixed solution can be 1 to 7; in some specific examples, the pH value of the mixed solution is 3 to 5. Thus, the effect of lithium recovery can be further improved.
[0115] In some embodiments, the solid-liquid ratio of the mixed solution can be 100 g / L to 300 g / L; in some other embodiments, the solid-liquid ratio of the mixed solution is 250 g / L to 300 g / L, specifically, 100 g / L, 120 g / L, 150 g / L, 180 g / L, 200 g / L, 220 g / L, 250 g / L, 280 g / L, 300 g / L, etc. Within this solid-liquid ratio range, the efficiency of lithium recovery is relatively high.
[0116] In some embodiments, the second stirring speed can be 400rpm~1000rpm (such as 400rpm, 500rpm, 600rpm, 700rpm, 800rpm, 900rpm or 1000rpm, etc.). In some embodiments, the second stirring time can be 10min~10h (such as 10min, 20min, 30min, 40min, 50min, 1h, 3h, 5h, 8h, 10h, etc.); in other embodiments, the second stirring time can be 10min~30min (such as 10min, 20min or 30min, etc.). Under the above reaction conditions, the reactants can be fully contacted, the reaction is more sufficient, and the reaction efficiency is higher.
[0117] In some embodiments, there is no particular limitation on the method of solid-liquid separation. As an example, the method of solid-liquid separation includes but is not limited to a Buchner funnel, a sand core funnel, a vacuum filter, a portable filtration device, a plate and frame filter press, a belt filter press, a box filter press, a diaphragm filter press, a skid-mounted filter press, etc. The filter media used in the filtration process include but are not limited to quantitative filter paper, qualitative filter paper, glass fiber filter membrane, nylon filter membrane, microporous filter membrane, filter cloth, filter plate, etc. In some embodiments, the maximum pore size of the filter medium does not exceed 47 microns. As an example, the pore size of the filter medium can be 0.45 microns.
[0118] S300: The lithium-rich mother liquor is concentrated and lithium is precipitated in sequence to obtain a lithium-containing product.
[0119] In some embodiments, the concentration and lithium precipitation include: continuously evaporating the lithium-rich mother liquor until turbidity occurs to obtain a concentrated solution; mixing the concentrated solution and a lithium precipitation promoter and performing a third stirring to obtain a lithium-containing product.
[0120] In some embodiments, the temperature of continuous evaporation is 90° C. to 105° C. (specifically, 90° C., 91° C., 92° C., 93° C., 94° C., 95° C., 96° C., 97° C., 98° C., 99° C., 100° C., 101° C., 102° C., 103° C., 104° C., 105° C., etc.) Within this temperature range, the solvent in the lithium-rich mother liquor can be quickly evaporated.
[0121] In some embodiments, the constant temperature device used to maintain continuous evaporation is not limited, including but not limited to a constant temperature oil bath, a constant temperature water bath, a heating table, a constant temperature heating mixer, a heating jacket, a high and low temperature constant temperature circulation device, a chemical reactor, etc., as long as it can meet the heating and heat preservation functions.
[0122] In some embodiments, the lithium precipitation promoter includes at least one of sodium carbonate, ammonium carbonate, potassium carbonate, and carbon dioxide. The main function of the lithium precipitation promoter is to provide carbonate radicals, which react with lithium ions in the lithium-rich mother liquor to form lithium carbonate precipitates.
[0123] It should be noted that, except for carbon dioxide, other carbonates of analytical purity or chemical purity can be used as lithium precipitation promoters, which are usually pre-dissolved in water to form a saturated solution, and then the lithium-rich mother liquor is added dropwise to the saturated carbonate solution under stirring to achieve rapid lithium carbonate precipitation. The carbon dioxide gas is transported in the form of compressed gas or liquid gas, with a gas concentration of ≥98%, and the ventilation flow rate can be adjusted according to the reaction vessel.
[0124] In some specific examples, in this step, the lithium-rich mother liquor can be kept warm at a reaction temperature of 90°C to 105°C and continuously evaporated until a white turbid substance appears. The purpose of evaporation is to reduce the solubility of lithium carbonate by reducing the solvent, thereby obtaining a higher lithium carbonate recovery rate. When enough white turbid substance is produced, a lithium precipitation promoter is added to the lithium-rich mother liquor. The main function of the lithium precipitation promoter is to provide carbonate ions, which react with lithium sulfate in the lithium-rich mother liquor to form a lithium carbonate precipitate.
[0125] In some embodiments, the molar ratio of the lithium precipitation promoter to the lithium element in the lithium-containing waste is 0.55-0.6:1, specifically 0.55:1, 0.56:1, 0.57:1, 0.58:1, 0.59:1, 0.6:1, etc. Within this ratio range, lithium can be fully precipitated, effectively improving the recovery rate of lithium.
[0126] In some embodiments, lithium precipitation includes: mixing a concentrated solution with a lithium precipitation promoter, and adjusting the pH of the resulting mixture to 8 to 10 (specifically 8, 8.5, 9, 9.5, 10, etc.), performing a third stirring, and obtaining a lithium-containing product. By adjusting the pH to 8 to 10, the precipitation of lithium carbonate is more conducive, and the recovery rate of lithium is further improved.
[0127] Specifically, there is no particular limitation on the pH regulator that can be used. As an example, the pH can be adjusted to 8-10 by sodium hydroxide. In this way, the pH can be effectively adjusted without introducing other impurities.
[0128] In some embodiments, the speed of the third stirring can be 400 rpm to 1000 rpm (such as 400 rpm, 500 rpm, 600 rpm, 700 rpm, 800 rpm, 900 rpm or 1000 rpm, etc.); the time of the third stirring is 30 min to 1 h (such as 30 min, 40 min, 50 min or 1 h, etc.). Under this condition, it is beneficial to precipitate the lithium-containing product, obtain a lithium-containing product with higher purity, and obtain a higher recovery rate.
[0129] It should be noted that the first stirring, the second stirring and the third stirring in this article can all be carried out by an agitator. There is no particular restriction on the specific type of the agitator. As an example, an agitator that achieves material dispersion and sufficient reaction through forced convection can be used, including but not limited to a magnetic agitator, a frame agitator, a top-entry agitator, a side-entry agitator, a chemical agitator, a paddle agitator or a circulating convection device.
[0130] In some embodiments, after the lithium precipitation step, the process further includes: dispersing the product of the lithium precipitation step with hot water at 50°C to 90°C (such as 50°C, 60°C, 70°C, 80°C or 90°C), filtering and drying in sequence to obtain a lithium-containing product. Since the lithium precipitation promoter is usually excessive and easily precipitates due to concentration, it is further stirred and dissolved with hot water at 50-90°C, and filtered and dried again, which is conducive to obtaining a high-purity lithium-containing product (in some specific examples, the purity of the lithium-containing product is 92.34% to 99.54%, and the sulfate concentration is less than 15ppm).
[0131] In the actual production process, preheating is first performed at a certain temperature and time to obtain a solution with a certain concentration of sulfate radicals in advance, and then mixing is performed to ensure that the sulfate radicals react with lithium iron phosphate first, and then the temperature is kept constant during the reaction process to ensure that sufficient sulfate radicals are continuously generated to participate in the reaction. Using sulfate radicals as oxides can further promote the oxidation of lithium iron phosphate and the leaching of lithium. After being leached, lithium will be adsorbed by the metal organic framework structure with rich pores and adsorption sites, and then lithium can be extracted and separated from the waste liquid through concentration and filtration.
[0132] In summary, the method for recovering lithium of the present application adopts the lithium adsorbent according to the embodiment of the present application. During the preheating process, the persulfate ion does not directly participate in the oxidation process, but acts as a precursor, and effectively promotes the breaking of the oxygen-oxygen bond in the persulfate ion by externally applying an energy exceeding the oxygen-oxygen bond energy in the persulfate ion (140 kJ / mol-213.3 kJ / mol), forming sulfate radicals and / or hydroxyl radicals with stronger electrophilic properties, which are used as the main oxidants of the reaction, and the sulfate radicals and / or hydroxyl radicals have strong selectivity, long half-life (40 μs), high oxidation potential (2.5 V)-3.1 V), and have a wider pH application range, etc. The efficiency of the original persulfate oxidation reaction of lithium iron phosphate is increased by 10 3 -10 5 The lithium recovery method of the present application can obtain a comparable or even higher lithium recovery rate and lithium product purity at a lower temperature and in a shorter time, and is extremely competitive in terms of production efficiency and cost reduction and efficiency improvement.
[0133] Specifically, compared with directly using persulfate, ozone, oxygen, hypochlorite, hydrogen peroxide, etc. as oxidants to react with lithium iron phosphate to recover lithium, the method of the present application can save at least 200.38 kWh of electricity (300 g / L) per ton of lithium iron phosphate powder processed.
[0134] The embodiments of the present application are described in detail below.
[0135] Example 1
[0136] Sodium persulfate and cobalt nitrate were added in a molar ratio of 4:1 to prepare a solution A with a total concentration of 1 mol / L, and the solvent was water. A 1 mol / L 2-methylimidazole organic solution (solution B) was prepared at room temperature, and the solvent was water. The solution B was gradually added dropwise to the stirred solution A at 400 rpm and 90 degrees Celsius, wherein the molar number of persulfate added to the solution A: the molar number of 2-methylimidazole in the solution B was 1:1. After stirring for 30 minutes, the obtained mixed solution C was concentrated and filtered to finally obtain the target product: Na 0.4 Co 0.1 S2O8 / MI, wherein MI is 2-methylimidazole.
[0137] Using waste lithium iron phosphate positive electrode sheets as raw materials, 0.5 mL min -1 After nitrogen was introduced for 2 hours at a flow rate of 10 °C min -1 The heating rate was raised to 450 °C and then kept at this temperature for 5 hours to obtain positive electrode powder and aluminum foil. A sufficient amount of lithium adsorbent Na 0.4 Co 0.1 S2O8 / MI was dissolved in water and kept at 60℃ for 5min. At the same time, the positive electrode powder was dissolved in water at the same temperature and kept warm. 0.4 Co 0.1 S2O8 / MI is fed in a sodium persulfate: lithium iron phosphate molar ratio of 0.55:1, solid-liquid ratio: 300gL -1 , stir at 60°C for 10 minutes and then filter to obtain filter cake (iron phosphorus slag) and mother liquor (lithium-rich mother liquor), respectively. The filter cake is dried and recovered, and the mother liquor is further concentrated at 90°C. When the solution is concentrated to have flocculent substances, an excess of saturated sodium carbonate solution (the molar ratio of sodium carbonate to lithium iron phosphate is about 0.55-0.6:1) is added to the lithium-rich mother liquor. The mixture is stirred at this temperature and evaporated continuously until a large amount of white crystals appear. A sand core funnel and a 0.45-micron water-washable filter membrane are used for suction filtration, and the solid powder on the dispersed filter membrane is washed with hot water above 50°C. The high-purity white powder, i.e., the lithium carbonate product, is obtained by repeated suction filtration.
[0138] Example 2-12
[0139] Same as Example 1, except that the type of persulfate, the type of transition metal salt, and the ratio of persulfate to transition metal salt are different, as shown in Table 1. Scanning electron microscope photos of the lithium adsorbents of Examples 3, 6, and 7 are shown in Table 1. Figure 2 , Figure 3 and Figure 4 .
[0140] Example 13
[0141] Same as Example 1, except that a sufficient amount of lithium adsorbent Na 0.4 Co 0.1 S2O8 / MI was dissolved in water and kept warm at room temperature for 5 minutes. At the same time, the positive electrode powder was dissolved in water at the same temperature and kept warm. The mixed solution containing the positive electrode powder and the lithium adsorbent was stirred at room temperature for 5 hours.
[0142] Comparative Examples 1-3
[0143] The same as Example 1, except that potassium persulfate, sodium persulfate and ammonium persulfate were used respectively and stirred for 5 hours under the same conditions at room temperature. The rest was the same as Example 1.
[0144] Test methods and results:
[0145] (1) Characterization of sulfate radical yield by complete capture method
[0146] The methanol complete capture method is based on the reaction process between methanol and sulfate radicals, which conforms to the following equation:
[0147] CH3OH+SO4 - =·CH2OH+SO4 2-
[0148] ·CH2OH=...=CH2O
[0149] In the preheated persulfate system, sulfate radicals can be captured by adding excess methanol. Before lithium iron phosphate is added to the water body, sulfate radicals react with methanol at a ratio of 1:1, and finally formaldehyde is generated at a ratio of 1:1. The amount of sulfate radicals generated in the reaction system can be inferred by detecting the amount of formaldehyde generated by liquid chromatography. The lithium adsorbent aqueous solutions corresponding to Examples 1-12 were heated to different stirring temperatures, and the sulfate radical concentration was measured. The test results are shown in Table 1.
[0150] Table 1. Sulfate radical yields at different temperatures
[0151]
[0152] The test results in Table 1 show that under room temperature, sulfate radicals are basically undetectable due to the lack of additional heat input, and lithium iron phosphate mainly reacts with persulfate. Properly increasing the temperature (at least ≥40°C) can obtain a higher sulfate radical yield in a shorter time, and preheating has a significant effect on promoting persulfate bond breaking to form sulfate radicals.
[0153] (2) Inductively coupled plasma spectrometer test
[0154] The filtered lithium-rich mother liquor and filter cake were subjected to inductively coupled plasma spectrometry testing for quantitative analysis of iron and lithium elements, and then compared with the three elements of the raw materials to obtain the leaching rates of iron, lithium and phosphorus in the lithium-rich mother liquor. The analysis results are shown in Table 2 below.
[0155] Table 2. Lithium and iron leaching rates of lithium-rich mother liquors of different embodiments under different temperature conditions
[0156]
[0157] The test results in Table 2 show that when the lithium adsorbent and lithium iron phosphate are reacted under conditions higher than room temperature, the concentration of sulfate radicals is higher, the lithium leaching efficiency and iron selectivity are better, and there are significant advantages compared with other persulfates at room temperature (Comparative Examples 1-3). This shows that the lithium adsorbent designed in the first aspect of the present application can generally improve the lithium recovery efficiency and selectivity of lithium-containing liquids, and through the process of the third aspect of the present application, appropriately increasing the temperature is sufficient to help obtain highly oxidizing sulfate radicals (Table 1), and is of great significance to cost savings and improved production efficiency.
[0158] (3) Nitrogen adsorption and desorption test
[0159] The nitrogen adsorption-desorption curve is used to characterize the specific surface area and porosity of the material. The test method refers to WIQC0000934. The test results of Examples 1-12 and Comparative Examples 1-3 are shown in Table 3 below.
[0160] Table 3. Specific surface area and porosity of lithium adsorbents in different examples and comparative examples
[0161] <h2 style=";text-align:left;direction:ltr"><![CDATA[M1 <h2 style=";text-align:left;direction:ltr"> a <h2 style=";text-align:left;direction:ltr"> M2<h2 style=";text-align:left;direction:ltr"> b <h2 style=";text-align:left;direction:ltr"> ]]><h2 style=";text-align:left;direction:ltr"> <![CDATA[Specific surface area m 2 / g]]> Porosity % Example 1 <![CDATA[Na 0.4 Co 0.1 ]]> 13.82 11.93 Example 2 <![CDATA[Na 0.3 Co 0.2 ]]> 15.74 13.07 Example 3 <![CDATA[Na 0.1 Co 0.1 ]]> 15.96 9.67 Example 4 <![CDATA[Na 0.2 Co 0.3 ]]> 15.41 9.49 Example 5 <![CDATA[Na 0.1 Co 0.4 ]]> 13.11 12.34 Example 6 <![CDATA[K 0.1 Co 0.1 ]]> 17.63 21.24 Example 7 <![CDATA[(NH4) 0.1 Co 0.1 ]]> 17.64 27.91 Example 8 <![CDATA[Na 0.1 Fe 0.1 ]]> 15.32 19.73 Example 9 <![CDATA[Na 0.1 Zn 0.1 ]]> 12.36 8.07 Example 10 <![CDATA[Na 0.1 Mn 0.1 ]]> 16.09 13.56 Embodiment 11 <![CDATA[Na 0.1 With 0.1 ]]> 12.08 14.58 Example 12 <![CDATA[Na 0.1 Cr 0.1 ]]> 13.95 26.33 Comparative Example 1 <![CDATA[Na2S2O4]]> 5.96 3.49 Comparative Example 2 <![CDATA[K2S2O4]]> 6.68 2.34 Comparative Example 3 <![CDATA[(NH4)2S2O4]]> 7.34 7.72
[0162] It can be found that in the presence of ligands, the specific surface area and porosity of all examples are greater than those of single persulfate, indicating that the metal organic framework structure can effectively provide sufficient specific surface area and pores as a lithium adsorbent, greatly improving the adsorption efficiency and recovery purity.
[0163] In the description of this specification, the terms "first" and "second" are used for descriptive purposes only and cannot be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In the description of this application, the meaning of "plurality" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined.
[0164] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0165] Although the embodiments of the present application have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be understood as limitations on the present application. Ordinary technicians in this field can change, modify, replace and modify the above embodiments within the scope of the present application.
Claims
1. A lithium adsorbent, characterized in that: It comprises a metal organic framework and a persulfate complexed on the metal organic framework; wherein, The metal organic framework comprises a complex of transition metal ions and organic molecular ligands.
2. The lithium adsorbent according to claim 1, characterized in that The persulfate includes at least one of ammonium persulfate, sodium persulfate, and potassium persulfate.
3. The lithium adsorbent according to claim 1, characterized in that The transition metal ions include at least one of Co, Fe, Zn, Mn, Cu, and Cr, preferably at least one of Co, Zn, and Fe.
4. The lithium adsorbent according to claim 1, characterized in that The organic molecular ligand includes 2-methylimidazole ligand.
5. The lithium adsorbent according to claim 1, characterized in that The complex has the following chemical formula: <h2 style=";text-align:left;direction:ltr">M1<h2 style=";text-align:left;direction:ltr"> a <h2 style=";text-align:left;direction:ltr"> M2<h2 style=";text-align:left;direction:ltr"> b <h2 style=";text-align:left;direction:ltr"> S2O8 / MI Among them, 1≥a≥0, 1≥b≥0, and a and b meet the requirements of chemical formula balancing; M1 includes at least one of NH4, Na, and K, M2 includes at least one of Co, Fe, Zn, Mn, Cu, and Cr, preferably at least one of Co, Zn, and Fe; MI includes 2-methylimidazole ligand.
6. The lithium adsorbent according to any one of claims 1 to 5, characterized in that The molar ratio of the persulfate to the transition metal ion in the persulfate is 4:1 to 1:4, preferably 2:3 to 1:4; and / or The molar ratio of the persulfate to the organic molecule is 1:10 to 1:1, preferably 1:4 to 1:
1.
7. The lithium adsorbent according to any one of claims 1 to 5, characterized in that The specific surface area of the lithium adsorbent is 12 m 2 / g~18m 2 / g; and / or The porosity of the lithium adsorbent is 8% to 30%.
8. The lithium adsorbent according to any one of claims 1 to 5, characterized in that Includes secondary particles formed by agglomeration of primary particles, wherein: The D of the primary particles 50 The particle size is 0.8 micrometer to 1.5 micrometer, preferably 1.0 micrometer to 1.2 micrometer; and / or The D of the secondary particles 50 The particle size is 5 microns to 15 microns, preferably 5 microns to 8 microns.
9. A method for preparing the lithium adsorbent according to any one of claims 1 to 8, characterized in that: include: mixing a persulfate, a transition metal salt and a solvent to obtain a mixed salt solution; mixing the organic molecular ligand with the solvent to obtain an organic solution; The mixed salt solution and the organic solution are mixed and first stirred, and the obtained mixture is concentrated and filtered in sequence to obtain the lithium adsorbent.
10. The method according to claim 9, characterized in that Mixing the mixed salt solution and the organic solution comprises: Under the heating and the first stirring conditions, the mixed salt solution is added dropwise to the organic solution.
11. The method according to claim 10, characterized in that The heating temperature is 90°C to 105°C; and / or The first stirring speed is 200 rpm to 600 rpm; and / or After the dropwise addition of the mixed salt solution is completed, the first stirring is continued for 30 min to 60 min.
12. The method according to claim 9, characterized in that The total concentration of salt in the mixed salt solution is 0.5 mol / L to 1 mol / L; and / or The transition metal salt includes at least one of nitrate, oxalate and sulfate, preferably nitrate; The concentration of the organic solution is 1 mol / L to 5 mol / L; The solvent includes at least one of alcohol and water, preferably water.
13. A method for extracting lithium from lithium-containing waste, characterized in that: include: Preheating a solution containing the lithium adsorbent according to any one of claims 1 to 8 and a solution containing lithium-containing waste respectively to obtain a preheated lithium adsorbent solution and a preheated lithium-containing solution; The preheated lithium adsorbent solution and the lithium-containing solution are mixed, and the obtained mixed solution is stirred for a second time while maintaining the preheating temperature, and solid-liquid separation is performed to obtain a solid material and a lithium-rich mother solution; The lithium-rich mother liquor is concentrated and lithium is precipitated in sequence to obtain a lithium-containing product.
14. The method according to claim 13, characterized in that The preheating temperature is 40°C to 90°C, preferably 40°C to 65°C, more preferably 60°C to 65°C; and / or The preheating time is 5 min to 10 min.
15. The method according to claim 13, characterized in that The preheated lithium adsorbent solution and the lithium-containing solution are mixed in a ratio of 1:0.55-1 in which the molar ratio of lithium element in the lithium-containing solution to persulfate in the lithium adsorbent solution is 1:0.55-1.
16. The method according to claim 13, characterized in that The pH value of the mixed solution is 1 to 14, preferably 1 to 7, more preferably 3 to 5; and / or The solid-liquid ratio of the mixed solution is 100 g / L to 300 g / L, preferably 250 g / L to 300 g / L.
17. The method according to claim 13, characterized in that The second stirring speed is 400 rpm to 1000 rpm; and / or The second stirring time is 10 min to 10 h, preferably 10 min to 30 min.
18. The method according to claim 13, characterized in that The concentration and precipitation of lithium include: The lithium-rich mother liquor is continuously evaporated until turbidity occurs to obtain a concentrated solution; The concentrated solution and the lithium precipitation accelerator are mixed and subjected to a third stirring to obtain the lithium-containing product.
19. The method according to claim 18, characterized in that The lithium immersion comprises: The concentrated solution and the lithium precipitation accelerator are mixed, and the pH of the obtained mixture is adjusted to 8-10, and the third stirring is performed to obtain the lithium-containing product.
20. The method according to claim 18, characterized in that The temperature of the continuous evaporation is 90°C to 105°C.
21. The method according to any one of claims 18 to 20, characterized in that: The lithium precipitation accelerator comprises at least one of sodium carbonate, ammonium carbonate, potassium carbonate and carbon dioxide; and / or The molar ratio of the lithium precipitation accelerator to the lithium element in the lithium-containing waste is 0.55-0.6:1; and / or The third stirring speed is 400 rpm to 1000 rpm; The third stirring time is 30 min to 1 h.
22. The method according to claim 13, characterized in that After the lithium precipitation step, the method further includes: dispersing the product of the lithium precipitation step with hot water at 50° C. to 90° C., and filtering and drying in sequence to obtain the lithium-containing product.
23. The method according to claim 13, characterized in that The lithium-containing waste material includes at least one of lithium iron phosphate battery positive electrode black powder and lithium iron phosphate battery positive and negative electrode waste powder.